Phthalocyanine-mediated Photodynamic Treatment of Tumoural and Non-tumoural cell lines - Manisova, Barbora; Binder, Svatopluk; Malina, Lukas; Jiravova, Jana; Langova, Katerina; Kolarova, Hana (Anticancer research, 2015)
This study deals with the use of cationic far-red absorbing photosensitizers (λ(max) ~740 nm) from the group of the phthalocyanines, in photodynamic therapy. The photosensitizers differed in their central atom, bearing either hydrogen, zinc or magnesium. These photosensitizers were tested in vitro on the tumour cell line HeLa (cervical cancer) and non-tumour cell line NIH3T3 (mouse fibroblast). The following tests were performed: measurement of reactive oxygen species production, viability testing, Comet assay and cell type detection (apoptotic, necrotic and living cells). The best results were achieved with zinc derivative at relatively low half-maximum inhibitory concentration (0.04 μM) and a total radiation dose of 15 J cm(-2).
Keywords: Photochemotherapy; Cell Line; Photosensitizer; NIH 3T3 Cells; fotosenzibilizující látky; Neoplasms; fotochemoterapie; Cell Line, Tumor; Photosensitizing Agents; reaktivní formy kyslíku; Isoindoles; photodynamic treatment; indoly; tumour cells; oxidative stress; hořčík; phototoxicity; Magnesium; isoindoly; HeLa buňky; cellular damage; Reactive Oxygen Species; Animals; lidé; Phthalocyanine; HeLa Cells; Humans; Indoles; zvířata; myši; buněčné linie; zinek; nádory; nádorové buněčné linie; Mice; Zinc; buňky NIH 3T3